Enterprise business process management in the public sector : the case of the Department of Human Services (DHS) Australia - Bandara, Wasana; Bailey, Scott; Mathiesen, Paul; Jones, Chris; McCarthy, Jo (London : Palgrave MacMillan UK, 2018)
This case is focused on the sustainable development and progression of enterprise business process management (EBPM) capabilities at the Federal Department of Human Services: a large Australian federal government agency. The detailed case narrative vividly describes the case organisation, their prior and present BPM practices and how they have attempted BPM at an enterprise level, capturing pros and cons of the journey.
Originally Published InBandara, W., Bailey, S., Mathiesen, P., Jones, C., & Jones, J. (2018). Enterprise business process management in the public sector: The case of the Department of Human Services (DHS) Australia. Journal of Information Technology Teaching Cases, 8, 217–231.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Australia. -- Department of Human Services -- Case studies; Human services -- Management -- Case studies